A comparative experimental study on the collection and analysis of DNA samples from under-fingernail materials - Yuksel, Elif; Karadayi, Sukriye; Ozbek, Tulin; Karadayi, Beytullah (OXFORD UNIV PRESS, 2025)
In cases of murder and rape where there is physical contact between the perpetrator and the victim, analysis of the victim's fingernail material is quite valuable. Although it is possible that the foreign DNA detected in the fingernail material does not belong to the perpetrator of the incident, if it does belong to the perpetrator of the incident, it may provide useful findings for solving the incident. Fingernail material collected after the incident often contains mixed DNA. The efficiency of sample collection procedures is of particular importance, as this process may pose some problems in the interpretation of autosomal short tandem repeat analyses used for the identification of the individual or individuals. The aim of this study is to compare three different fingernail material collection procedures (thick-tipped swabbing, thin-tipped swabbing and nail clipping) to determine the most efficient sample collection procedure and to contribute to routine investigations to identify the assailant in forensic cases. In our study, under-fingernail materials was collected from 12 volunteer couples by three different methods. To help compare the efficiency of the three different methods, the profiles obtained were classified based on the number of female and male alleles detected. In the obtained short tandem repeat profiles, while nail clipping yielded 58.3% (n= 7) High level DNA mixture as a profile containing 12 or >12 female alleles, 75% (n= 9) of the samples taken with cotton-toothpick swabs (thin-tipped) yielded Full male profile. In conclusion, our study shows that cotton-toothpick swabs (thin-tipped) are the most efficient method for determining the male DNA profile among three different fingernail material collection procedures. We suggest that using thin-tipped swabs produced in a specific standard, instead of the standard swabs commonly used in routine crime investigations, to identify perpetrators from fingernail material may improve the efficiency of processing nail material and evaluating evidence.
Keywords: forensic genetic; STR typing; fingernail material; swab; PREVALENCE; PROFILES; Legal Medicine